2012
DOI: 10.3109/17435390.2012.741724
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ZnO and TiO2nanoparticles: physicochemical characterisation and toxicological effects on human colon carcinoma cells

Abstract: Despite human gastrointestinal exposure to nanoparticles (NPs), data on NPs toxicity in intestinal cells are quite scanty. In this study we evaluated the toxicity induced by zinc oxide (ZnO) and titanium dioxide (TiO₂) NPs on Caco-2 cells. Only ZnO NPs produced significant cytotoxicity, evaluated by two different assays. The presence of foetal calf serum in culture medium significantly reduced ZnO NPs toxicity as well as ion leakage and NP-cell interaction. The two NPs increased the intracellular amount of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 48 publications
4
92
0
1
Order By: Relevance
“…47 TiO2 at concentrations of 1-20 µg/cm 2 had no effect on Caco-2 cell viability in the presence or absence of serum. 40 TiO2 at loadings of 0.1-100 mg/L did not influence Caco-2 cell viability, as measured by MTT assay. 41 TiO2 at loading levels of 1-mixtures, similar to the NP examined in the present study, did not induce toxicity (by LDH assay) to Caco-2 cells at loading levels of 20 µg/cm 2 , but toxicity was observed at 80 µg/cm 2 .…”
Section: Particle Uptake By Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 TiO2 at concentrations of 1-20 µg/cm 2 had no effect on Caco-2 cell viability in the presence or absence of serum. 40 TiO2 at loadings of 0.1-100 mg/L did not influence Caco-2 cell viability, as measured by MTT assay. 41 TiO2 at loading levels of 1-mixtures, similar to the NP examined in the present study, did not induce toxicity (by LDH assay) to Caco-2 cells at loading levels of 20 µg/cm 2 , but toxicity was observed at 80 µg/cm 2 .…”
Section: Particle Uptake By Cellsmentioning
confidence: 99%
“…Infrared spectrum ( Figure 3B) shows that upon suspension in serum, characteristic protein bands 31 are observed on the ZnO. It has been proposed that the presence of serum proteins will inhibit dissolution of ZnO, 40 however it is unlikely that serum can stabilize against dissolution in the highly acidic pepsin solution.…”
Section: Particle Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies have demonstrated the undesirable toxic effects of ZnO NPs, such as the induction of oxidative stress, autophagic cell death, inflammatory responses, cellular damage and genotoxicity. [9][10][11][12][13] The toxicity of ZnO NPs has been shown to be attributed to the dissolution of Zn to free Zn 2+ ions and the generation of free radicals from the surface of ZnO, resulting in cellular ionic and metabolic imbalance that is associated with a defect in ionic homeostasis and an inhibition of ion transport. 9,12,14,15 In vitro toxicity studies revealed that generation of reactive oxygen species (ROS), followed by ROS-induced oxidative stress, is the mechanism leading to the ZnO NP-mediated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the phase (amorphous, anatase, etc) and contact area between a single nanoparticle (NP) and a single cell, smaller and rod shaped nano ZnO (in comparison to spherical shape) is reported to be more toxic. [15][16][17] The surface charge of NPs is also an important factor in considering the toxicity, as the positively charged NPs were shown to possess a higher toxicity, 9 and differential surface charge is attributed to the cellular uptake and intracellular localization. 18 The toxic effects of in vivo exposure have been reported in vertebrates such as rodent 6 and zebra fish, 19,20 as well as the invertebrate the fruit fly Drosophila melanogaster.…”
Section: Introductionmentioning
confidence: 99%